Do Political Parties Matter? Evidence from U.S. Cities* - Ferreira, Fernando; Gyourko, Joseph (Quarterly Journal of Economics, 2009)
Are cities as politically polarized as states and countries? “No” is the answer from our regression discontinuity design analysis, which shows that whether the mayor is a Democrat or a Republican does not affect the size of city government, the allocation of local public spending, or crime rates. However, there is a substantial incumbent effect for mayors. We investigate three mechanisms that could account for the striking lack of partisan impact at the local level, and find the most support for Tiebout competition among localities within metropolitan areas.